Temperament and Character Traits of Female Eating Disorder Patients with(out) Non-Suicidal Self-Injury - Buelens, Tinne (J Clin Med, 2020)
Eating disorder (ED) patients show alarmingly high prevalence rates of Non-Suicidal Self-Injury (NSSI). Adolescents seem to be particularly at risk, as EDs and NSSI both have their onset in mid-adolescence. It has been suggested that personality could be a transdiagnostic mechanism underlying both EDs and NSSI. However, little attention has been given to adolescent clinical samples compared to adult and/or community samples. Therefore, the current study investigated the role of personality in a sample of 189 female inpatients with an ED (M = 15.93, SD = 0.98). Our results confirmed the high prevalence of NSSI in EDs, specifically in patients with bingeing/purging behaviours (ED-BP). Temperamental differences were found between ED-BP and the restrictive ED subtype (ED-R). Namely, ED-BP patients showed more harm avoidance and less self-directedness compared to ED-R. Temperamental differences were found in NSSI as well, regardless of ED subtype: ED patients who had engaged in NSSI during their lifetime reported less self-directedness and more harm avoidance. Interestingly, only ED patients who recently engaged in NSSI showed less novelty seeking. These temperamental profiles should be recognised as key mechanisms in the treatment of adolescent ED patients with and without NSSI.